Legal Implications of Extension of Time in Power Plant Construction Projects: A Comparative Study of FIDIC and Indonesian Law - Indahwati, Amaliyah Noor; Baroroh, Eric; Wisnuaji, Haryo; Sumantri, Mahfiar Fajar Akbar; Hardjomuljadi, Sarwono; Sami’an, S. (SIGn Journal of Social Science, 2025)
Disputes related to EoT in electricity EPC projects frequently escalate due to normative conflicts. This conflict arises between the time-bar clause in the FIDIC international contract standards, characterized by strict liability, and the principle of equity in Indonesian civil law. This research aims to analyze the validity of the time-bar clause in light of the principle of good faith, qualify the characteristics of excusable delay in concurrent delay situations, and reconstruct effective dispute-resolution mechanisms. The research method employed is a normative juridical approach, with comparative and empirical case study methods, applied to power plant projects. The results indicate that the application of claim rights forfeiture sanctions due to administrative notification delays possesses conditionally binding force. Such provisions can be set aside if the Service User is proven to have violated the prevention principle. Furthermore, in concurrent delay situations, national law mandates the proportional application of the apportionment principle. This research also finds that the Standing Dispute Board, as provided for in PUPR Ministerial Regulation Number 11 of 2021, is a more effective preventive instrument than arbitration for maintaining project cash flow liquidity. It is concluded that legal harmonization through teleological contract interpretation and the strengthening of Dispute Board executive regulations is imperative. The implications of these findings demand that stakeholders revise the Particular Conditions of contract to accommodate equitable administrative flexibility, ensuring legal certainty and the sustainability of national strategic infrastructure.